Bio-inductive implant for rotator cuff repair: our experience and technical notes. - Micheloni, Gian Mario; Salmaso, Gianpaolo; Zecchinato, Gino; Giaretta, Stefano; Barison, Elia; Momoli, Alberto (Acta Biomedica Atenei Parmensis, 2020)
The treatment of chonic large and partial rotator cuff tears represents a common challenge for orthopedic surgeons. Numerous treatments were suggested but the best is still controversial. Into this field the use of an augment for rotator cuff repair aims to protect the tension of the suture in the postoperative phase and to facilitate the biological healing process. In our institution we treated 4 patients (3 males and 1 female) with rotator cuff tear with bio-inductive implant. All patients presented with a postero-superior rotator cuff tear: 3 patients with a type C-III tear according to Snyder classification and 1 patient with partial articular tear with significant degeneration and poor tendon quality (type A-III tear according to Snyder classification). The final outcome is highly satisfying intraoperatively and the postoperative protocol reflects our normal postoperative protocol following to rotator cuff repair. No complications occurred at 6 months follow-up. The use of the bio-inductive implant in the arthroscopic rotator cuff repair resulted easy, rapid and reproducible. Although no current scientific evidences regarding such implants exist, in selected cases and with the correct indications, the use of bio-inductive implant could represent an effective aid and an option in case of complex rotator cuff tears